ANALISIS KEPATUHAN SYARIAH, KUALITAS LAYANAN, DAN CSR TERHADAP PEMBENTUKAN CITRA BSI DI JABODETABEK - Abdullah Najib Azzamani; Hartutik Hartutik (Media Riset Bisnis Manajemen Akuntansi, 2026)
This study aims to analyze the effect of Sharia compliance, service quality, and Corporate Social Responsibility (CSR) on the image of Bank Syariah Indonesia (BSI) in the Jabodetabek area. The research uses a quantitative approach with a descriptive-associative design and data collected from 100 respondents through questionnaires. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that Sharia compliance has a positive and significant effect on BSI’s image, indicating that adherence to Islamic principles is the main determinant in shaping public perception and trust. Meanwhile, service quality and CSR do not have a significant effect on BSI’s image, suggesting that these factors are perceived as basic expectations rather than strategic differentiators. These findings highlight that the image of Islamic banking is more influenced by value-based legitimacy rooted in religious principles than by performance-based factors. The study contributes to the development of stakeholder and legitimacy theories in the context of Islamic banking and provides practical implications for strengthening Sharia compliance as a core strategy in enhancing corporate imageKeywords : corporate social responsibility, service quality, sharia compliance, bank image, BSI